Wheat Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Ibendahl, Gregg (My University, 2015)
This publication provides estimated cost and returns for forward farm planning for wheat in north central Kansas.
MF2158_2015_04
Keywords: MF2158; Crops; Economics; MF